(untitled) (Third Sector Social Economic Review, 2026)
This study examines the effect of digital content exposure on compulsive buying behavior among young adults within the context of food and beverage marketing. Quantitative data were collected through an online survey from 495 young adults aged 18–30 across Türkiye. The Digital Marketing Content Exposure Scale developed for this research consists of three sub-dimensions (Active Engagement-Based Exposure, Targeted Channel Exposure, and General Digital Environment Exposure), while compulsive buying behavior is addressed through the sub-dimensions of “Loss of Control and Consequences” and “Obsessive Buying.” Findings from the simple linear regression analysis indicate that digital content exposure has a significant and positive effect on compulsive buying behavior (β = 0.441; p < 0.001). According to the multiple regression results, Active Engagement-Based Exposure is the strongest predictor of both sub-dimensions of compulsive buying. Targeted Channel Exposure also has a significant effect on both sub-dimensions, whereas General Digital Environment Exposure is significant only for “Obsessive Buying.” Overall, the results reveal that digital marketing content creates notable psychological effects on the purchasing behavior of young adults. The findings underscore the importance of ethical digital marketing practices for marketing professionals and policymakers and provide recommendations aimed at protecting young consumers.